FORMATION OF THE NATIONAL AND CULTURAL CONTEXTS IN THE MNEMONIC DISCOURSE - S. G. Kuzmina (Вестник Кемеровского государственного университета, 2016)
The paper is based on the material of mnemonic texts created by representatives of Russian, Polish and Lithuanian national cultures. The aim of the paper is to justify the influence of the national mentality on the cognitive process of memory by fixing the linguistic means of actualization of national and international components in the mnemonic author’s linguistic picture of the world, and fixing the features of their appeal to national and cultural realities. The main methods of the research are the descriptive analysis, the analysis of the context, and the method of quantification. Results of the research are made through the discourse projection, continuing the development of the concepts “mnemonic discourse” and “cognitive and speech subject” in relation to the mnemonic narrator. The paper proves the fact of influence of the features of the mnemonic narrator’s mentality (which includes both the national self-identification, and the experience of international relations) on the cognitive process of reminiscence, and demonstrates the process of creation of national and cultural contexts in the mnemonic discourse.